2010
DOI: 10.1007/s10096-010-1000-5
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin resistance and vancomycin heteroresistance in Staphylococcus aureus in cystic fibrosis patients

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) infections are increasingly being reported among cystic fibrosis (CF) populations worldwide. In this paper, we sought to examine at the epidemiology, the molecular characterisation and the antibiotic resistance of MRSA isolates in our cohort of CF patients. All MRSA strains were collected prospectively at the University Hospital of Catania, Italy, during a two-year study between mid 2005 to mid 2007 and underwent molecular, pathotype and susceptibility charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
3
25
1
Order By: Relevance
“…We detected a higher and stronger biofilm production in CF patients than in non-CF patients. Cafiso et al [12] also stated that all strains isolated from CF patients were medium or strong biofilm producers and this result seemed to be consistent with the ability of these microorganisms to adhere and persist in the lungs of these patients.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…We detected a higher and stronger biofilm production in CF patients than in non-CF patients. Cafiso et al [12] also stated that all strains isolated from CF patients were medium or strong biofilm producers and this result seemed to be consistent with the ability of these microorganisms to adhere and persist in the lungs of these patients.…”
Section: Discussionmentioning
confidence: 56%
“…This result is similar with findings of Molina et al [11] who detected PVL gene in any of the 98 MRSA-CF isolates but described a multiresistant biofilm forming clone in most of the patients. In a period between 2005 and 2007, 64 CF patients in Italy were screened and PVL was detected in only 2 isolates [12]. Elizur et al [6] described the emergence of PVL + MRSA infection in 15% of CF patients and demonstrated that the patients who acquired a PVL + organism were more likely to have a focal pulmonary infiltrate on chest radiograph, a markedly greater decline in FEV 1 suggesting that early identification and treatment of CF patients with newly acquired PVL + MRSA may be crucial.…”
Section: Discussionmentioning
confidence: 99%
“…The first glycopeptide-intermediate S. aureus strain with a vancomycin MIC of 4 to 8 mg/liter was isolated from a CF patient in 1999. Since then, several additional cases in CF patients were reported; vancomycin heteroresistance has been observed in approximately 3% to 5% of CF patients harboring S. aureus (112)(113)(114)(115)(116)(117).…”
Section: Heteroresistance a Resistance Reservoir Without Selective Pmentioning
confidence: 99%
“…In clinical situations, certain patient populations, such as cystic fibrosis patients, are more chronically exposed to beta-lactam antibiotics than others. In this context, h-VISA strains have been isolated from patients who were not previously exposed to glycopeptides (12,13). A retrospective study of cystic fibrosis patients' clinical characteristics that was conducted at our hospital suggested that ceftazidime (CAZ), a beta-lactam largely used to treat Pseudomonas aeruginosa infections in such patients, may be a risk factor for the development of h-VISA (14).…”
mentioning
confidence: 99%